Impact of the COVID-19 Pandemic on the Mental Health of College Students: A Systematic Review and Meta-Analysis - Li, Yang; Wang, Aiwen; Wu, Yalin; Han, Nana; Huang, Huiming (Frontiers in Psychology, 2021)
Background: The COVID-19 pandemic has been spreading and brought unprecedented psychological pressure on people across the entire globe since last December. Objectives: To synthesize the existing evidence on the prevalence of mental health status during the epidemic, and provide the basis for mental health education. Materials and methods: The literature search was conducted in 9 databases from December 2019 to October 2020. The risk of bias for each study was assessed and the random-effects meta-analysis was used to estimate the prevalence of specific mental health problems. The review protocol was registered in PROSPERO with the registration number CRD42020208619. Results: 27 studies were included in the analysis with a total of 706,415 participants combined, and 14 mental health problems were gathered. Meta-analysis showed that the prevalence of depression was 39% (95% CI: 27% - 51%) and that of anxiety was 36% (95% CI: 26% - 46%). Sub-group analysis indicated that the prevalence of depression and anxiety varied with nations and survey date. The prevalences of depression (60%, 95% CI: 46%-74%) and anxiety (60%, 95% CI: 46%-74%) in non-Chinese college students were higher than those in Chinese college students (26%, 95% CI: 21%-30% and 20%, 95% CI: 14%-26%). The proportion of depression (54%,95% CI: 40%-67%) and anxiety (37%, 95% CI: 26%-48%) were higher after March 1st than before it (21%,95% CI: 16%-25% and 19%, 95% CI: 13%-25%). Conclusions: The meta-analysis results presented that the prevalence of depression (39%) or anxiety(36%) among college students was getting increased during the COVID-19 pandemic. In addition, the mental health of college students is affected by the nations and survey date. It was necessary to establish ways to mitigate mental health risks under pandemic conditions.